Purinergic P2 Receptors: Novel Mediators of Mechanotransduction - Kong, Qihang; Quan, Yue; Tian, Geer; Zhou, Junteng; Liu, Xiaojing (Frontiers in Pharmacology, 2021)
Mechanosensing and mechanotransduction are vital processes in mechanobiology and play critical roles in regulating cellular behaviour and fate. There is increasing evidence that purinergic P2 receptors, members of the purinergic family, play a crucial role in cellular mechanotransduction. Thus, information on the specific mechanism of P2 receptor-mediated mechanotransduction would be valuable. In this review, we focus on purinergic P2 receptor signalling pathways and describe in detail the interaction of P2 receptors with other mechanosensitive molecules, including transient receptor potential channels, integrins, caveolae-associated proteins and hemichannels. In addition, we review the activation of purinergic P2 receptors and the role of various P2 receptors in the regulation of various pathophysiological processes induced by mechanical stimuli.